Diffuse Meningiomatosis without Neurofibromatosis: A Rare Diagnosis with Atypical Presentation - Sharma, Smily; Sharma, Pankaj; Kumar, Amit (Indian Journal of Radiology and Imaging, 2021)
Meningiomas are amongst the most common neoplasms of the central nervous system; however, “multiple meningiomas” or “meningiomatosis” account for < 10% of cases. The association with neurofibromatosis 2 is seen in ∼50% of cases. We report a case of 35-year-old female patient who presented with left eye proptosis, left forehead swelling, and multiple cranial nerve palsies predominantly on the left side. Imaging evaluation revealed innumerable en plaque meningiomas forming a sheet-like nodular thickening along the dura, causing marked hyperostosis and extending into the orbits, cavernous sinuses, sellar–suprasellar regions, various skull foramina, basal cisterns and into the cervical spinal canal causing mass effect on vital structures of the brain and cervical spinal cord. Similar lesions were found scattered in rest of the spine. We intend to highlight the role of imaging in accurately establishing the diagnosis and evaluating the extent and burden of disease in such rare cases.
Keywords: en plaque meningioma; meningiomatosis; neurofibromatosis 2